One-member sentences in belle-lettres style (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The paper deals with the peculiarities of functioning of one-member sentences in   the texts of belle-lettres style. It proves that one-member sentences are the means of expressive syntax and,  depending on semantic-and-grammatical realization, they express subject-and-objective modality.
Keywords: definite personal; indefinit personal; generalized personal; impersonal; infinitive; nominative sentences; expressive syntax